Obspack CO2 time-series result from Hyltemossa (30.0 m) - Michal Heliasz; Tobias Biermann; Meelis Molder; ICOS RI (Integrated Carbon Observation System, 2025)
This data file contains high accuracy European ObsPack observational timeseries in netCDF format of ambient mole fraction of co2 in dry air collected at Hyltemossa (30.0 m). The measurements were calibrated using the WMO GAW calibration scale WMO CO2 X2019. Included are (all whenever available) historical PI QCed data, ICOS Level 2 data, ICOS FastTrack data and ICOS NRT data. It is part of the 2025.3 FastTrack update of the Globalview EU CO2 data product and is intended for use in carbon cycle inverse modeling, model evaluation, and satellite validation studies. Metadata for the full co2 product release are available at https://commons.datacite.org/doi.org/10.18160/R0PE-1H0Z. Please also visit http://www.gml.noaa.gov/ccgg/obspack/ for more information. If you use these data in your research, please consider citing the full ObsPack release that this file is part of (https://commons.datacite.org/doi.org/10.18160/46ST-DEVK).
ICOS RI, Heliasz, M., Biermann, T., Molder, M. (2025). Obspack CO2 time-series result from Hyltemossa (30.0 m), 2016-12-13–2025-10-01, European ObsPack, https://hdl.handle.net/11676/kzP-BxpsSNxyv01UVV1wugaN
Keywords: Carbon Portal; CO2; ICOS; Obspack; WMO CO2 X2019; atmospheric dry air co2 mole fraction; time series; time instant, UTC; time instant, UTC; CO2 (dry air mole fraction); CO2 (dry air mole fraction); quality flag; quality flag; data level (Obspack); data level (Obspack); standard deviation of gas mole fraction; standard deviation of gas mole fraction; ICOS mole fraction uncertainty metrics; ICOS mole fraction uncertainty metrics; Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap